-6g+36=-5g+8g

Simple and best practice solution for -6g+36=-5g+8g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6g+36=-5g+8g equation:


Simplifying
-6g + 36 = -5g + 8g

Reorder the terms:
36 + -6g = -5g + 8g

Combine like terms: -5g + 8g = 3g
36 + -6g = 3g

Solving
36 + -6g = 3g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-3g' to each side of the equation.
36 + -6g + -3g = 3g + -3g

Combine like terms: -6g + -3g = -9g
36 + -9g = 3g + -3g

Combine like terms: 3g + -3g = 0
36 + -9g = 0

Add '-36' to each side of the equation.
36 + -36 + -9g = 0 + -36

Combine like terms: 36 + -36 = 0
0 + -9g = 0 + -36
-9g = 0 + -36

Combine like terms: 0 + -36 = -36
-9g = -36

Divide each side by '-9'.
g = 4

Simplifying
g = 4

See similar equations:

| 16y*3=25y | | -6g+8=-6g+8g | | A^2-29a=-100 | | 3.4/4=x/7 | | -8g+6=-6g+1g | | 8+10y=12 | | 8+3(x-2)=-10 | | -c/4=-4 | | 1200=200-(m/50) | | 2x^2+5=-6x | | (3/x)+3=(3/4x)+(25/8) | | 3*2+6*8+6*2= | | 3r^2+4r+5=0 | | 13x+23y=144 | | (3/x)+3=(3/4x)+25/8 | | (r/12)+600=1200 | | y-5=-5+-y | | -5/3r-2r=-11/9 | | A-6a+9a=0 | | 6.5-4/5= | | 3(x-2)=-5+2(x+3) | | 6x-18=4(x+2) | | -12/5f=-5/7 | | A-6a+9a= | | 9x+19=6x-15 | | 7x-5x+2(4x-3)=6(2x+5)-(7x+9) | | 4=m/3-6 | | 1.5x=2+.5x | | 15x^2-46xy+35y^2=0 | | 2/3e=-3/4 | | 5x-4x=16x+3 | | y-5=5+-y |

Equations solver categories